Improving Quality of Islamic Education Through Community Based Education: Principal Engagement - Arbi Arbi (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2018)
The emergence of a community-based education paradigm is triggered by a large flow of modernization and democratization. Education should be decentralized. Its implementation in schools should be collaborative, and the principal has a big hand in this. Therefore, this study aims to examine the involvement or participation of the principal in improving the quality of Islamic Religious Education (PAI) community-based in junior high school. The data are collected through in-depth interviews, observations, literature studies and documentation instruments. This study shows that the principal's concern on religious affairs and the improvement of the quality of PAI learning is relatively high. This can be seen from his programs conducting recitation on Islamic and national holidays, Dhuha studies, tahfidz one day one verse, book of yaumi and verse book, tajwid learning or tahsin for teachers, qurban animal repayment and highly motivating teachers to have skills, develop existing curriculum, and improve the competence of teaching based on social piety.